Reflections of agile governance in public services in the digital age - Dewi, Luh Putu Regita Septa; Suardana, Ida Bagus Raka (Universitas Merdeka Malang, 2023)
The Covid-19 pandemic has prohibited us a lot in terms of bureaucratic governance where the bureaucracy must remain at the forefront in providing public services, such as optimization of ICT. The transformation of public services in e-government is directed at the implementation of flexible governance, so in this era of disruption, agile governance is needed and is a necessity in facing a crisis of existence for a country. This study aims to analyze how prepared the Disdikpora Bali Province is for Agile governance by upgrading public service quality, and services transformation and analyzing the obstacles or challenges that occur. Research using a qualitative-descriptive and inductive approach. Data was obtained using in-depth interviews and then analyzed using triangulation. Results show the level of readiness of the Bali Province Disdikporain realizing Agile governance in upgrading public service quality during the Digital Age can be said to be quite ready. The transformation of services from conventional to digitalization has been implemented and Bali ProvinceDisdikpora can respond and make adjustments to the changes that occur. The transformations carried out include the implementation of e-kepegawaian, e-aset, and e-DUPAK services. The lack of human capability in using ICT, inadequate infrastructure, and unstable internet connections are challenges in realizing Agile Governance.